ANALISIS EFEK PENDINGIN KONVEKSI PAKSA MENGGUNAKAN JET SINTETIK NOZZLE X - Ibnu Drajat Wijatama (2020)
Some electronic components have a heat limit so that the electronics can work well, the heat that occurs affect the quality and effectiveness of the electronic device. therefore, cooling of electronic components has become an important part of electronic technology. Natural cooling is heat transfer without the aid of tools, but natural cooling has shortcomings that require a long time and forced convection cooling is heat transfer by means of air flow with the help of tools such as fans, but the fans have relatively large dimensions. Therefore, research into alternative methods of forced convection cooling using synthetic jets as a form of innovation in cooling. This study aims to find the characteristics of the Nozzle X. the selection of the optimum frequency for the cooling process and the optimum height of the synthetic jet nozzle to the flat plate. There were 2 methods used in this research, namely data collection directly and computer-based for CFD. The use of X-form nozzle had the characteristics that using a frequency of 100 Hz and a height of 4 cm was able to decrease quickly.